2014
DOI: 10.1136/heartjnl-2013-304893
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammation and brachial artery endothelial function in the Multi-Ethnic Study of Atherosclerosis (MESA)

Abstract: In this multi-ethnic cohort, increased levels of the pro-inflammatory cytokine IL-6 were associated with impaired endothelial function assessed by FMD. Elevated IL-6 levels may reflect a state that promotes vascular inflammation and development of subclinical atherosclerosis independent of traditional cardiovascular risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 27 publications
5
30
0
1
Order By: Relevance
“…This is consistent with a large cross-sectional study conducted in 5314 people undergoing health screening which showed age as an independent predictor of FMD [34]. According to previous works conducted on non-AF patients [35][36][37], also in our AF population baseline brachial diameter was inversely associated with FMD. Nevertheless, despite some evidences suggesting a predictive role of brachial diameter on CV events [38], in the present study we did not find an independent association between basal brachial diameter and CV events at multivariate analysis.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with a large cross-sectional study conducted in 5314 people undergoing health screening which showed age as an independent predictor of FMD [34]. According to previous works conducted on non-AF patients [35][36][37], also in our AF population baseline brachial diameter was inversely associated with FMD. Nevertheless, despite some evidences suggesting a predictive role of brachial diameter on CV events [38], in the present study we did not find an independent association between basal brachial diameter and CV events at multivariate analysis.…”
Section: Discussionsupporting
confidence: 92%
“…Prior work showed a modest association between IL-6 and TNF-Ī± with impaired endothelial function, atherosclerotic calcification, and subclinical and clinical cardiovascular disease 2 20 26. Parallel with those studies, we found that elevations in both pro-inflammatory cytokines had elevated baseline CAC.…”
Section: Discussionsupporting
confidence: 86%
“…PDE-5 inhibitors, in the paradigm of statins, may have a significant impact in stabilizing plaques by decreasing acute inflammatory activation [11,28]. Also, as we and others have shown, they are able to improve endothelial dysfunction [7][8][9][10] and aortic stiffness [12][13][14][15] that are predictors of cardiovascular events [29][30][31]; this may be partially mediated through their antiinflammatory properties [16][17][18]. Such effects are promptly evident, a factor of crucial significance for prevention of events with acute nature such as cardiovascular ones [32,33].…”
Section: Discussionmentioning
confidence: 88%
“…Given the unfavorable influence of inflammation on arterial function [16][17][18], the aforementioned effects of PDE-5 inhibitors could be partly attributed to a robust anti-inflammatory action. Indeed, previous studies reported a chronic effect of sildenafil and tadalafil on endothelial function and pro-inflammatory markers/mediators including intercellular and vascular cell adhesion molecules-1 (ICAM-1 and VCAM-1, respectively), high sensitivity C-reactive protein (hsCRP), and interleukin-6 (IL-6) [11].…”
Section: Introductionmentioning
confidence: 99%